Evaluasi Geotagging Pada Aplikasi Smile di BPJS Ketenagakerjaan Tanjung Morawa Menggunakan Metode Human Centered Design - Rahma, Baqiyatur; Putri, Raissa Amanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The SMILE application (Worker Protection Information System) is a special application belonging to the Tanjung Morawa Branch of Employment BPJS which has been integrated with all Employment BPJS companies. The SMILE application system can be used to transfer membership, check membership status and be used for updating data, correcting internal office data, updating data and geotagging. However, the SMILE application still has problems when doing geotagging, namely on the display and maps to find the address point for the company's location. The author aims to evaluate the geotagging interface in the SMILE application using Human Centered Design. HCD (Human Centered Design) is a method which in its process is based on the general natural characteristics of humans with the hope of creating a system based on user needs and being able to solve problems and constraints faced by users. The author is not at the real development stage, because the application currently running has a lot of data so it will be risky if development is carried out, without careful calculations. Based on user feedback with a total of 5 respondents. The final result is in the form of a prototype based on user interface evaluation using the HCD method as a reference material for improving the SMILE application. Keyword: Human Centered Design, Geotagging, SMILE Aplication